Republic of Fiji : 2010 Article IV Consultation-Staff Report and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Fiji's economy has contracted by 3 percent in 2009, and marginal growth is estimated for 2010. Foreign exchange reserves have improved steadily following the April 2009 devaluation and stood at over 4 months of imports (USD 710 million) at end 2010. Fiji's economic growth was low in the past few years and the structure of the economy remained broadly unchanged. The weak business climate results in sluggish private investment and is the major impediment to economic growth in Fiji. Fiji's economy--especially tourism and finance--is linked closely to its regional neighbors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet